Online Education for Public Health Capacity Building in Low- to Middle-Income Countries: The Peoples-uni Experience - Heller, Richard F; Strobl, Judith; Madhok, Rajan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
People’s Open Access Education Initiative (Peoples-uni, http://peoples-uni.org) aims to contribute to improvements in the health of populations in low- to middle-income countries by building public health capacity via e-learning at affordable cost. We describe experience over nine years of the initiative, including the development and delivery of a Master of Public Health (MPH) programme in public health and collaboration with a UK University. Courses rely on Open Educational Resources and volunteer tutors from over 50 countries to date. During 18 semesters since 2008, 1619 students from 92 countries (71% from Africa) enrolled. Of 128 students accepted on an MPH programme accredited by a UK University, 94 earned an MPH (73%) and a further 18 (14%) achieved a postgraduate diploma or certificate. Other developments include continuing involvement with Alumni, and a sister site for Open Online Courses to include topics not often found in MPH courses. We offer insights for further development of this and similar online capacity building programmes within low-resource environments. Our experience shows the feasibility of affordable, high quality online education and that there is scope for accelerating capacity building programmes through partnerships with higher education institutions and health(care) organisations.